Vertex and edge Co-PI indices of bridge graphs - Devi, Sharmila; Kaladevi, V. (International Journal of Advanced Mathematical Sciences, 2016)
The Co-PI index of a graph G is denoted by Co-PI(G) and  is defined as Co-PI(G  is the number of vertices of G whose distance to the vertex u is less than the distance to the vertex v in G. Similarly, the edge Co-PI index of G is defined as Co-PIe(G) is number of edges of G whose distance  to the vertex u is less than the distance to the vertex v in G.  In this paper, the upper bounds for the Co-PI and edge Co-PI indices of bridge graph are obtained.